Sensor de presença baseado em resposta acústica do ambiente - Ribeiro, Danillo José Cezar (2019)
Wave propagation that necessarily depends on the geometry of the environment is a more or less well-defined problem. However applications that depend on this feature are difficult to implement and susceptible to many types of interference. This propagation in a spreader environment often produces extremely complex response signals that are characteristic of each geometry, its physical properties and sensitive to disturbances that may occur. We propose to use the characteristics of this spreader environment to construct a presence sensing system that emits a set of beeps capable of identifying changes caused, for example, by an unauthorized person in a private environment or by accidents that modify this geometry. From calibration, control and testing steps, this system is capable of detecting and possibly alerting secondary systems of improper presence. This work applies relatively simple mathematical sound analysis techniques for this purpose and can be implemented on existing hardware such as computers and mobile phones.